Development and discontent in tribal India - Yatindra Singh Sisodia; Tapas Kumar Dalapati (Rawat, 2015)
Contributed papers presented at a seminar titled Development and Discontent in Tribal India held at Madhya Pradesh Institute of Social Science Research, Ujjain in the year 2012.